The state of lipoperoxidation processes in boys with obesity - M. A. Darenskaya; O. A. Gavrilova; L. A. Grebenkina; O. V. Kravtsova; L. V. Natyaganova (Acta Biomedica Scientifica, 2017)
The problem of obesity is extremely relevant for modern medical science and healthcare, and child and adolescent obesity deserves special attention. It seems to be interesting to trace the interrelation of pathological processes in obesity in the form of metabolic disorders at the level of the organism and at the cell level - disorders in the system of lipid peroxidation. Studies in adolescent boys are relevant, as there has been a general increase in the incidence in this age category. The purpose of the research was to study the state of the system "lipid peroxidation - antioxidant protection" in adolescent boys with exogenous-constitutional obesity. 19 adolescent boys with obesity were examined in comparison with the control group. Spectrophotometric and fluorometric methods of examination were used. An increase in the level of secondary lipid peroxidation products - ketodienes and conjugated trienes (1.65 times) - was revealed in adolescent boys with obesity. In the antioxidant defense system, differences in this group included reduced values of α-tocopherol (1.42 times), retinol (1.51 times) and superoxide dismutase activity (1.19 times), in the absence of statistically significant changes in the total antioxidant activity (AOA) in blood and components of glutathione status. The revealed disorders allow to recommend the complex therapy including prescription of antioxidants and medicines directed on normalization of lipid exchange at the given category of patients.